Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsieh, Hsueh-Han; Chuang, Ming-Hsiu; Shih, Yung-Yen; Weerakkody, W. Sanjaya; Huang, Wei-Jen; Hung, Chin-Chang; Muller, François L. L.; Ranatunga, R. R. M. K. P.; Wijethunga, D. S. (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll-a (Chl-a), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.